Primary school teacher´s evaluation of risk behaviour in younger school age - Lucia Pašková (Psychology and its Contexts, 2018)
In the last few years, it was recorded a significant increase of aggression, bullying, intolerance and other forms of inappropriate behaviour in children in primary and secondary schools. Problems at schools which are solved too late, or more often not solved at all, frequently cause not only the masking of these phenomena and thus provide support to aggressors but also the demotivation of teachers, burnout syndrome, dissatisfaction at work and so on. This study is trying to analyse an incidence of problem behaviour pupils in younger school age. Its aim is to present the results of our broadly conceived research which had the goal of ascertaining the opinions of teachers on the characteristics of aggression in younger schoolage pupils and the evaluation of risky behaviour of pupils by the primary school teachers. To get this information, was used a scale of risky behaviour (Mezera et al., 2000). The research sample consisted of 118 younger school-age children in the third and fourth classes and of teachers from the primary schools in the Slovak. It was 74 boys and 44 girls with problems in behaviour. Based on our findings and observation of intersexual differences, it is possible to say that in the research sample, boys achieved higher mean scores in all categories. In the process of verification of statistical significant differences, such differences were indicated in favour of boys in all categories of risky behaviour except that of egocentric behaviour. These findings correspond with those of Verešová (2002), Slovíková (2013) as well as Čerešník and Gatial (2014), who researched the pubescent population. Statistically significant differences (0.05) in favour of boys were found in the following variables: asocial behaviour, antisocial behaviour, impulsive behaviour, maladaptive behaviour, negativistic behaviour, and inclination to a problem group. The authors acknowledges the limits of their research due to which it is not possible to further categorise and compare the research sample according to the class or the school the pupils attend. Therefore is possible propose that further research should be undertaken with focus on pupils’ conduct grade and disciplinary measures (not) imposed on them as well as on the extent of their unexcused lesson absence. The results of research confirmed the necessity to pay the same kind of attention to both boys’ and girls´ expressions of aggression and do not attribute aggressive behaviour to boys more than to girls.